A study of terminology describing treaty relationships between Israel and her neighbours during the Israelite monarchy - Burden, J. J.(Jasper Jacobus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD) -- University of Stellenbosch, 1970.